2022
DOI: 10.26719/emhj.22.057
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of private healthcare sector in reproductive, maternal, newborn, child and adolescent health in selected Eastern Mediterranean countries

Abstract: Background: The private healthcare sector in the Eastern Mediterranean Region (EMR) is active and growing, providing curative, preventive, and promotive services related to reproductive, maternal, newborn, child, and adolescent health (RMNCAH). Aims: To understand the contribution of formal for-profit private health-care sector in delivering RMNCAH services and explore best practices for improvement. Methods: Desk review of available literature from Saudi Arabia, Oman, Iraq, Egypt, Sudan, Yemen, Pakistan, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several countries, including Iraq (an upper-middle-income country in the Middle East), have seen a rapidly expanding private sector involved in the delivery and acceptance of basic health services over the past decade [ 10 , 11 ]. A study of 70 countries revealed that the private health care industry is accountable for the delivery of more than a third of the world's maternal health care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several countries, including Iraq (an upper-middle-income country in the Middle East), have seen a rapidly expanding private sector involved in the delivery and acceptance of basic health services over the past decade [ 10 , 11 ]. A study of 70 countries revealed that the private health care industry is accountable for the delivery of more than a third of the world's maternal health care [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines are based on best practices and recommendations from the WHO and other international agencies for planning and managing pregnancy and childbirth ( MOH, 2016 ). These guidelines are part of Oman's effort to adopt UNs’ sustainable development goals that aim to reduce U5MR to < 25 per 1000 and MMR to 70 per 100 000 live births by 2030 ( Iqbal et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%